Pembelajaran Interaktif Dengan Mengunakan Strategi Card Sort Pada Mata Pelajaran Ipas Kelas V Mis Miftahul Khoir Rasau Jaya - Naila Muqarriba; Salito (putrapublisher.org, 2024)
This study aims to determine the impact of implementing the Card Sort strategy in Science learning (IPA) in grade V at MIS Miftahul Khoir Rasau Jaya. The Science learning at this school previously faced challenges related to low student engagement and difficulty in understanding abstract concepts. The Card Sort strategy was applied to improve student involvement, understanding of the material, and social skills such as collaboration and communication. This research used a qualitative approach with a descriptive research type. The results showed that the implementation of the Card Sort strategy significantly increased student engagement in Science learning. Students, who were previously passive, became more active in group discussions and concept sorting. This strategy also helped students understand Science material more deeply, particularly in connecting related concepts. Furthermore, Card Sort encouraged students to collaborate in groups, enhancing their collaboration and communication skills. Student motivation also improved, as the learning became more interactive and enjoyable. The implementation of this method also led to improved learning outcomes, as evidenced by tests showing better comprehension of Science material. Therefore, the Card Sort strategy was proven effective in enhancing the quality of Science learning in grade V at MIS Miftahul Khoir Rasau Jaya.